Annual changes in composition and abundance of the Cladoceran planktonic community (Crustacea: Anomopoda y Ctenopoda) and water chemistry in Don Tomás lake (La Pampa, Argentina) (Semiárida, 2020)
Variations in the taxonomic composition and densities of the species of the community of planktonic cladocerans of a low salinity pond of La Pampa province were analyzed over a one year period on the basis of monthly samplings. Diversity and species richness were higher than in other provincial water bodies, probably ow into the low salinity of this water body. Nine species were recorded: Moina micrura Kurz, 1874, Bosmina huaronensis Delachaux, 1918, Afona sp. Baird, 1843, Macrothrix sp. Baird, 1843, Leydigia feydigi Schoedler, 1863, Ceriodaphnia cf. Dubia Richard, 1895, Daphnia cf.obtusa Kurz,1874, Daphnia spinufata Birabén, 1917 y Diaphanosoma birgei Korínek, 1981. Although the planktonic species B. huaronensis was dominant, the ticoplankter Afona sp. also attained high densities. D. birgei, registered in other ponds of the province with different physical and chemical characteristics was also recorded in the studied pondo Most of the detected species were small, probably owing to the effect of selective predation by fish.
Keywords: Crustaceans; Cladocerans